Avaliação da formação acadêmica de egressos pós-graduados em odontologia de uma instituição de ensino superior. - Pinheiro, Joana Karla de Assis (2020)
In view of the current economic scenario, postgraduate education is one of the greatest challenges in education in Brazil. Even with all the cuts that the sector has suffered, it is still the path for millions of Brazilians who wants a job and better salaries in the country. It is salutary to mention that the market is dynamic and requires professionals with solid, quality training that meets their demands. Therefore, there is an urgent importance to investigate the path that the student takes during his academic transition, always in the expectation that the training received has been the best possible. Thus, the concern with the quality of the training process has been one of the main objectives of Higher Education Institutions that aim to train professionals recognized for their excellence. Notwithstanding what governs the national scenario, the Graduate Program in Dentistry (PPGO) of the Federal University of Ceará (UFC) plays an important role in the training of qualified masters and doctors at the Northeast level, since it is among the few Programs in the region that have doctoral level courses. By understanding that the graduate, due to his academic experience, is a reliable and critical source, this study aimed to assess the perception of graduate students in Dentistry about their academic training, with a view to maintaining and improving the quality of the Program. The guiding question was: What is the perception of the alumni about the academic training received in the graduate program in Dentistry at UFC? To this end, a field research was carried out, with a quantitative and qualitative approach, considering the universe of students graduating from 2015 to 2019 (N = 123), in which a questionnaire based on the Higher Education Performance (HEdPERF) model was applied, with 39 objective and 2 subjective questions, sent through Google Forms. The study had the participation of 43 respondents (35% of the universe) and found that the graduates, in general, are satisfied with the aspects considered in the research. It can be inferred that the non-academic aspects adhere to the satisfaction index of the graduate of the PPGO, contributing for the academic formation to be successful. On the other hand, the programmatic contents constitute weaknesses of the program, since they were the most negatively evaluated. However, the results found reaffirm PPGO's commitment to give society a professional with high scientific knowledge